2013
DOI: 10.1063/1.4795156
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature giant electrocaloric properties of relaxor ferroelectric 0.93PMN-0.07PT thin film

Abstract: In this paper, 0.93PMN-0.07PT thin film shows a giant electrocaloric effect at room temperature. At electric field shift of 723 kV/cm, the peak value of ΔS of 0.93PMN-0.07PT thin film is 13.05 J/K.kg. The largest change (12.24 °C in 15.18 V, i.e. 0.8 K/V) at TC = 27 °C is more than the previous results obtained in giant electrocaloric PbZr0.95Ti0.05O3 films near the ferroelectric Curie temperature of 222°C (12 K in 25 V, i.e. 0.48 K/V) [A.S. Mischenko, et.al. Science 311, 1270 (2006)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The search of new cooling principles based on solidstate phenomena and development of ecologically friendly refrigerators with the lowest power consumption are very important tasks for modern refrigeration [1][2][3][4][5][6][7][8][9][10][11][12].The magnetocaloric effect (MCE) is either an isothermal magnetic entropy change or an adiabatic temperature change, Physics Department, Faculty of Science, Tanta University, Tanta, Egypt obtained by applying an external magnetic field [13][14][15][16]. Behavior and application of the magnetic properties of ferromagnetic materials become more and more important as magnetoelectronic devices for the level of miniaturization and reliability necessary for commercialization [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The search of new cooling principles based on solidstate phenomena and development of ecologically friendly refrigerators with the lowest power consumption are very important tasks for modern refrigeration [1][2][3][4][5][6][7][8][9][10][11][12].The magnetocaloric effect (MCE) is either an isothermal magnetic entropy change or an adiabatic temperature change, Physics Department, Faculty of Science, Tanta University, Tanta, Egypt obtained by applying an external magnetic field [13][14][15][16]. Behavior and application of the magnetic properties of ferromagnetic materials become more and more important as magnetoelectronic devices for the level of miniaturization and reliability necessary for commercialization [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[33], the dashed line is a fourth-polynomial method result and the single line represent simulated data using this model. It is found that, the maximum of temperature change ( T  ) is much lower than that reported in work [33], but close to the one reported in Science where a fourth-polynomial was used [31]. In addition, the corresponding maximum of temperature change ( T  ) in our work are near the experiment result, i.e.…”
Section: The Electrocaloric Effectmentioning
confidence: 99%
“…Thus, doping with Ba0.67Sr0.33TiO3 (BST67), Ba0.71Sr0.29TiO3 (BST71), Ba0.74Sr0.26TiO3 (BST74), Ba0.77Sr0.23TiO3 (BST77) increases the intensity of the electrical field induction D which carries to enhanced ECE with quite low electric field applied. Another material chosen for the paper's purposes is 0.93PMN-0.07PT thin film [39,40] because of its giant ECE at 27°C. It is made up of the PbMg2/3Nb1/3O3 relaxor ceramic, filled with PbTiO3 (PT), to achieve a wide-range of dipolar ordering.…”
Section: The Most Promising Magnetocaloric and Electrocaloric Materialsmentioning
confidence: 99%